2011
DOI: 10.1093/fampra/cmr017
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cognitive behavioural therapy in primary health care: a review

Abstract: CBT delivered in primary care, especially including computer- or Internet-based self-help programs, is potentially more effective than usual care and could be delivered effectively by primary care therapists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 77 publications
2
82
0
7
Order By: Relevance
“…The results are in line with those from a meta-analyses which showed that psychotherapy (including, but not limited to CBT) is effective for depression symptoms in primary care (40,41), a meta-analyses which showed that brief psychotherapy (including, but not limited to CBT) is effective for both anxiety and depression symptoms in primary care (42), and a systematic review which showed that CBT is effective for anxiety and depression symptoms in primary care (7). What is unique about this study is that it reviewed through meta-analysis CBT's effectiveness in primary care for anxiety and depression symptoms, across delivery formats and also in specific delivery formats (e.g.…”
Section: Comparison With Existing Literaturesupporting
confidence: 86%
See 2 more Smart Citations
“…The results are in line with those from a meta-analyses which showed that psychotherapy (including, but not limited to CBT) is effective for depression symptoms in primary care (40,41), a meta-analyses which showed that brief psychotherapy (including, but not limited to CBT) is effective for both anxiety and depression symptoms in primary care (42), and a systematic review which showed that CBT is effective for anxiety and depression symptoms in primary care (7). What is unique about this study is that it reviewed through meta-analysis CBT's effectiveness in primary care for anxiety and depression symptoms, across delivery formats and also in specific delivery formats (e.g.…”
Section: Comparison With Existing Literaturesupporting
confidence: 86%
“…Despite its increased provision in primary care, the vast majority of research on CBT has focused on one-to-one CBT, in specialized mental health services (7). The few available evaluations of CBT's effectiveness in primary care have yielded positive results, for example, a systematic review indicating that CBT is effective for symptoms of anxiety and depression in primary care (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is strong support for CBT in the treatment of a series of conditions, including anxiety, panic, depressive symptoms (103)(104)(105), and NCCP (106). A Cochrane review found CBT useful and moderately successful, despite the multifaceted aetiology in NCCP (107).…”
Section: Management Of Non-cardiac Chest Painmentioning
confidence: 99%
“…Therapist guided Internet-delivered CBT is similar to face-to-face treatment with regard to treatment effects (115)(116)(117)(118)(119), despite different therapist backgrounds (120)(121)(122). Guided Internet-delivered CBT has been proven to be effective in the treatment of mild to moderate symptoms of depression and anxiety (104,123), and does not differ from face-to-face treatment. However, there is a big difference between guided and unguided Internet-delivered CBT (115,124).…”
Section: Cognitive Behavioural Therapymentioning
confidence: 99%